The Law Enforcement against the Personnel of Corruption Crime - Haris Fadillah Harahap; Widayati Widayati (Law Development Journal, 2021)
The purpose of this research is to analyze and explain: 1) Implementation of law enforcement against perpetrators of corruption in the jurisdiction of the Pemalang District Prosecutor's Office, 2) Efforts made by the Prosecutor in preventing the occurrence of criminal acts of corruption in the jurisdiction of the Pemalang District Attorney that hinders law enforcement against perpetrators of corruption in the jurisdiction of the Pemalang District Prosecutor's Office and the solution. The approach method used in this study is a sociological juridical approach. The sociological juridical approach method is used to study/analyze secondary data in the form of legal materials, especially primary legal materials and secondary legal materials. The results showed that the implementation of law enforcement against perpetrators of corruption in the jurisdiction of the Pemalang District Prosecutor's Office noted that carry out several processes or stages in accordance with the laws and regulations and the Prosecutor's Standard Operating Procedure (SOP), namely examination, investigation, investigation and prosecution. As for prosecution, in addition to criminal efforts, efforts were also made to force the return of money from corruption to be returned to the state treasury. As for the efforts made by the Prosecutor in preventing the occurrence of criminal acts of corruption in the jurisdiction of the Pemalang District Prosecutor's Office, namely through comprehensive policies and comprehensive administrative reform in the form of privatization, deregulation, and decentralization. Factors that hinder law enforcement against perpetrators Criminal acts of corruption in the jurisdiction of the Pemalang District Attorney are the complexity of corruption cases, time constraints, the intensity of examinations by the limited functional supervisory apparatus, the spread of corruption cases through public policies, and the level of public legal awareness is still relatively low.